Responsibilities And Werda Notary's Legal Protection for Deeds He Made While Still Serving as a Notary - Al Majid, Muchammad Bachtiar; Hafidz, Jawade (TABELLIUS: Journal of Law, 2023)
Responsibility and legal protection in the UUJN only regulates "notaries who are still in office", not "notaries whose term of office has ended". This research aims to determine the responsibilities of retired notaries regarding deeds made while still in office and their form. legal protection for retired notaries for deeds made while still in office. The research method in this study uses a normative juridical approach, research specifications use descriptive analysis, data sources and data collection techniques use secondary data taken through literature study and data analysis uses qualitative analysis. The results of the research show that a retired notary remains responsible for deeds made while still in office until he dies. Meanwhile, the form of legal protection for retired Notaries is contained in the Memorandum of Understanding between the Indonesian National Police and INI number: 01/MOU/PPINI/V/2006 and in Article 66 UUJN. This article means that legal protection applies to notaries who are still serving and those who have retired. Because the responsibility of a notary is lifelong, the legal protection for notaries in Article 66 UUJN also applies until the notary dies. Keywords: Notary; Protection; Responsibility; Werda.